2020
DOI: 10.5194/esd-11-903-2020
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic impact of ENSO and IOD on Indian summer monsoon rainfall in observations and climate simulations – an information theory perspective

Abstract: Abstract. The El Niño–Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) are two well-known temporal oscillations in sea surface temperature (SST), which are both thought to influence the interannual variability of Indian summer monsoon rainfall (ISMR). Until now, there has been no measure to assess the simultaneous information exchange (IE) from both ENSO and IOD to ISMR. This study explores the information exchange from two source variables (ENSO and IOD) to one target (ISMR). First, in order to illus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 70 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…But, when changing the resolution or slightly altering the model configuration, the performance is only marginally modified, compared to if a substantial adjustment is done in the model configuration (such as coupling to a different land model as done for AUS-44), this can alter the performance substantially. The results from this large COSMO-CLM model ensemble indicate that an RCM-modeler can do a lot when it comes to improve the model performance, but if there is information missing in the large-scale GCM forcing on the RCM boundaries, it should not be expected that the RCMs can improve on that (Hall, 2014;Pothapakula et al, 2020;Rana et al, 2020 GCM performance for each region should be considered, or, whether the spread to include GCM´s sensitivity to increasing greenhouse gasses and other forcings (Rineau et al, 2019) should also be evaluated when selecting driving data. We propose that the planning of the GCM-RCM model chain should be done through coordination between the GCM and RCM-modelers, so that we can obtain a model chain that we trust in and is capturing the range of possible future scenarios (Knutti, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…But, when changing the resolution or slightly altering the model configuration, the performance is only marginally modified, compared to if a substantial adjustment is done in the model configuration (such as coupling to a different land model as done for AUS-44), this can alter the performance substantially. The results from this large COSMO-CLM model ensemble indicate that an RCM-modeler can do a lot when it comes to improve the model performance, but if there is information missing in the large-scale GCM forcing on the RCM boundaries, it should not be expected that the RCMs can improve on that (Hall, 2014;Pothapakula et al, 2020;Rana et al, 2020 GCM performance for each region should be considered, or, whether the spread to include GCM´s sensitivity to increasing greenhouse gasses and other forcings (Rineau et al, 2019) should also be evaluated when selecting driving data. We propose that the planning of the GCM-RCM model chain should be done through coordination between the GCM and RCM-modelers, so that we can obtain a model chain that we trust in and is capturing the range of possible future scenarios (Knutti, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…The model versions used for CORDEX-simulations are COSMO-CLM4-8-17 (Panitz et al, 2014;Keuler et al, 2016;Di Virgilio et al, 2019;Hirsch et al, 2019), multiple versions of COSMO-CLM5 (Sørland et al, 2018;Li et al, 2018) and the accelerated version COSMO-crCLIM (Vautard et al, 2020;Pothapakula et al, 2020). The following sections give short descriptions of the different versions, their main model developments, and new options for different configurations.…”
Section: Cosmo-clm Description Developments and Versionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the influence of La Niña, which always modulates precipitation of oceanic origin that is the most important source of precipitation in the tropical north and south Atlantic Ocean, an increase in precipitation is usually observed. 52 Likewise, there is a significant relationship between the ENSO and precipitation in Asia; 53 particularly, the ENSO contributes to Indian monsoon interannual variability, 18,54 bringing about an increase in the precipitation over the Indian Peninsula during La Niña events. In this region, the influence of recycling supports the importance of precipitation from terrestrial origin.…”
Section: Discussionmentioning
confidence: 99%
“…Over Europe, groups were encouraged to perform additional simulations at 0.11 • (∼ 12 km) horizontal resolution (Jacob et al, 2020), although Kotlarski et al (2014) for Europe as well as Panitz et al (2014) for Africa found no significant added value in the mean fields with an increase in horizontal resolution. However, added value is found for extreme events and over complex terrain when the grid is refined from 0.44 to 0.11 • over Europe (Prein et al, 2016;Torma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%